Colonial Phantoms : Belonging and Refusal in the Dominican Americas, from the 19th Century to the Present - Ramírez, Dixa (Book collections on Project MUSE., 2018)
Using a blend of historical and literary analysis, Colonial Phantoms reveals how Western discourses have ghosted--miscategorized or erased--the Dominican Republic since the nineteenth century despite its central place in the architecture of the Americas. Through a variety of Dominican cultural texts, from literature to public monuments to musical performance, it illuminates the Dominican quest for legibility and resistance.